Bacterial endophytes: An agroecological alternative in the growth promotion and plant health management of cabbage leaf (Brassica oleracea var. acephala) (Research, Society and Development, 2021)
Among the most economically significant agricultural crops, the species of the Brassicaceae family stand out as one of the most popular in human food. Cabbage leaf (Brassica oleracea var. acephala) is an essential ingredient in many regional dishes and is an excellent nutritional source for children, young and old. However, Brazilian production has been suffering from the incidence of pests and diseases that affect the crop, being the black rot of the cruciferous (BRC), the main cause of economic losses of its producers. Given this context, the objective is to build a theoretical framework by reviewing the literature on the agroecological management of BRC in cabbage leaf, based on the contribution of scientific knowledge to the preservation of agrobiodiversity in rural and traditional family communities.